(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The system provides users with essential operations for handling book records, such as adding, removing, searching, and displaying books. Each book is represented as a node in a linked list, which includes details such as the book’s ID, title, author, and a pointer to the next node. This structure enables dynamic data management and flexibility in handling collections of book records. Key operations in the system include adding a book to the catalog by creating a new node and appending it to the end of the linked list. Removing a book is accomplished by searching for its ID and deleting the corresponding node from the list. Users can also search for a book by its ID, allowing for quick retrieval of details. Additionally, the system enables the display of all books in the catalog by traversing the entire linked list. To ensure efficient memory management, the system includes functionality to free allocated memory after operations are completed, preventing memory leaks. The project demonstrates the advantages of linked lists in managing dynamic collections of data, showcasing their flexibility and efficiency. Future enhancements could include implementing features such as sorting the catalog, improving search functionality to allow searches by title or author, updating book information, and handling errors like duplicate IDs. Designed to be simple, user-friendly, and scalable, this system offers a practical solution for managing book catalogs, making it suitable for various applications.